Comprehensive review on the molecular genetics of autosomal recessive primary microcephaly (MCPH) - Naveed, Muhammad (Genet Res (Camb), 2018)
Primary microcephaly (MCPH) is an autosomal recessive sporadic neurodevelopmental ailment with a trivial head size characteristic that is below 3–4 standard deviations. MCPH is the smaller upshot of an architecturally normal brain; a significant decrease in size is seen in the cerebral cortex. At birth MCPH presents with non-progressive mental retardation, while secondary microcephaly (onset after birth) presents with and without other syndromic features. MCPH is a neurogenic mitotic syndrome nevertheless pretentious patients demonstrate normal neuronal migration, neuronal apoptosis and neural function. Eighteen MCPH loci (MCPH1–MCPH18) have been mapped to date from various populations around the world and contain the following genes: Microcephalin, WDR62, CDK5RAP2, CASC5, ASPM, CENPJ, STIL, CEP135, CEP152, ZNF335, PHC1, CDK6, CENPE, SASS6, MFSD2A, ANKLE2, CIT and WDFY3, clarifying our understanding about the molecular basis of microcephaly genetic disorder. It has previously been reported that phenotype disease is caused by MCB gene mutations and the causes of this phenotype are disarrangement of positions and organization of chromosomes during the cell cycle as a result of mutated DNA, centriole duplication, neurogenesis, neuronal migration, microtubule dynamics, transcriptional control and the cell cycle checkpoint having some invisible centrosomal process that can manage the number of neurons that are produced by neuronal precursor cells. Furthermore, researchers inform us about the clinical management of families that are suffering from MCPH. Establishment of both molecular understanding and genetic advocating may help to decrease the rate of this ailment. This current review study examines newly identified genes along with previously identified genes involved in autosomal recessive MCPH.